Angioimmunoblastic lymphadenopathy associated with polyarthritis. Issue 4 (August 1980) - Rothwell, R S; Mant, M J; Davis, P
Abstract : A patient with angioimmunoblastic lymphadenopathy with dysproteinaemia is described. The patient had a severe clinical illness with a pronounced haemolytic anaemia, which followed well-established polyarthritis and gold therapy. It was accompanied by in-vitro evidence of suppressed cell-mediated immune responses and by development of serum antismooth muscle antibodies. These features are unusual and support theories that this disease has an immunological basis. Improvement occurred with prednisone and azathioprine therapy, suggesting that combined use of these agents is useful in some patients with AILD. The patient subsequently developed a lymphoma.